2018
DOI: 10.1177/0009922818803397
|View full text |Cite
|
Sign up to set email alerts
|

Using a Clinical Decision Support Tool to Increase Chlamydia Screening Across a Large Primary Care Pediatric Network

Abstract: We aim to demonstrate increased chlamydia screening across a large pediatric network using an electronic health record–based intervention. We developed a pop-up notification that alerted providers that chlamydia screening was recommended during a well adolescent visit, when appropriate. We compared chlamydia screening rates before and after the implementation of the alert. The screening rate for chlamydia improved from 2.40% in the year before intervention to 5.01% in the year after intervention (P < .01). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
8
0
5
Order By: Relevance
“…Chadwick et al 16 created a standardized, computer-generated laboratory order sheet to reduce incomplete testing and changed their testing policy from “opt-in” to “opt-out.” This program led to an STI testing rate increase from 5.5% to 45.2%. In addition, Karas et al 25 implemented the use of an electronic health record–based clinical decision support tool to increase annual chlamydia screening in a primary care pediatric network. This system provided alerts for sexually active females presenting for well care visits who had not had an annual chlamydia screening.…”
Section: Resultsmentioning
confidence: 99%
“…Chadwick et al 16 created a standardized, computer-generated laboratory order sheet to reduce incomplete testing and changed their testing policy from “opt-in” to “opt-out.” This program led to an STI testing rate increase from 5.5% to 45.2%. In addition, Karas et al 25 implemented the use of an electronic health record–based clinical decision support tool to increase annual chlamydia screening in a primary care pediatric network. This system provided alerts for sexually active females presenting for well care visits who had not had an annual chlamydia screening.…”
Section: Resultsmentioning
confidence: 99%
“… 28 Karas et al further demonstrated the impact of CDS in a pediatric primary care network by doubling the Chlamydia screening rates for at-risk patients. 29 McGrath et al reported the CDS impact on lead screening in primary care settings in a small study that utilized provider reminders to increase ordered screens from 21 to 49% but with less impact on actual testing results (17% baseline to 18% postintervention). 24 We believe our study demonstrates a more significant impact on lead screening in a larger primary care practice network.…”
Section: Discussionmentioning
confidence: 99%
“…Na primeira categoria, foram alocados artigos que relatavam estudos sobre diferentes tipos e aplicações de sistemas de apoio à decisão, que podem ser definidos como "processo para CAPÍTULO i aeaeaeaeaeaea melhorar as decisões e ações relacionadas à saúde, com conhecimento clínico organizado e informação para melhorar a saúde e a prestação de cuidados de saúde" (KARAS et al, 2018).…”
Section: Tipos Aplicações E Finalidades De Sistemas De Apoio à Decisãounclassified
“…Quanto ao tipo, os estudos incluem ferramentas do tipo software (Rubin et al, 2021;Thompson et al, 2021;McParland;Cooper;Johnston, 2019;Harry et al, 2022;KARAS et al, 2018), questionários avaliativos físicos (Mendonça et al, 2020) ou digitais (Lovgren et al, 2017), algoritmos de machine learning (Shimpi et al, 2019;Shimpi et al, 2022) e textos explicativos (Santos et al, 2022).…”
Section: Tipos Aplicações E Finalidades De Sistemas De Apoio à Decisãounclassified
See 1 more Smart Citation